#TITLE_ALTERNATIVE# - LAI (NIM 10107040); Pembimbing : Pr. Dr. Hendra Gunawan, LESLIE
In this thesis, the author will introduce an inequality discovered by S. S. Dragomir and A. McAndrew. This inequality is derived from a GrussÃ‚Â’ type inequality which is sharp. The results of Dragomir and McAndrew lead to three corollaries, namely in the case f of bounded,f' integrable, and f'q integrable. But, the question is whether these three corollaries are sharp. An inequality is considered to be sharp if in general equality are satisfied in certain cases. The sharp inequality gives us a better estimate. In this thesis, the author finds the general form of the three corollaries (found by Dragomir and Andrew) that can be modified to become sharp inequalities. In addition, the author also finds a few sharp inequalities in certain cases.